OCUPAÇÃO DE RIOS URBANOS: ESTUDO DO RIO SANTA MARIA DO DOCE EM COLATINA-ES - Gualberto, Lívia Barcelos; Albani, Vivian (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Brazil's urban rivers are known for environmental degradation problems, mainly because of the disorderly growth of cities. This research aims at analyzing the situation of the Santa Maria do Doce river, a tributary of the Doce River, which undergoes a severe water crisis and anthropic action for decades. That being preserved, it would serve as a viable alternative of water abstraction for the population of Colatina-ES, mainly after the rupture of the dams in Mariana- MG. The study included the analysis of the river slope areas in the urban area of Colatina, identifying areas with risk of flooding, the relationship between buildings and the river bank, analysis of legislation and identification of sewage points. The method used was bibliographic research, photographic records, and periodical visits to the field as well as public institutions. After analyzing data, it was noticed the inadequate distance between the river and the buildings, disrespecting the law n ° 12.651 / 2012 on permanent preservation areas, that results in the flood of buildings in the rainy season and degradation of the river. This research propose alternatives to preserve this river by exposing the necessity of understanding the occupation around it and its current environmental conditions.